Knowledge Management and Safety Compliance in a High-Risk Distributed Organizational System - Leif Jarle Gressgård (Safety and Health at Work, 2014)
Background: In a safety perspective, efficient knowledge management is important for learning purposes and thus to prevent errors from occurring repeatedly. The relationship between knowledge exchange among employees and safety behavior may be of particular importance in distributed organizational systems where similar high-risk activities take place at several locations. This study develops and tests hypotheses concerning the relationship between knowledge exchange systems usage, knowledge exchange in the organizational system, and safety compliance. Methods: The operational context of the study is petroleum drilling and well operations involving distributed high-risk activities. The hypotheses are tested by use of survey data collected from a large petroleum operator company and eight of its main contractors. Results: The results show that safety compliance is influenced by use of knowledge exchange systems and degree of knowledge exchange in the organizational system, both within and between units. System usage is the most important predictor, and safety compliance seems to be more strongly related to knowledge exchange within units than knowledge exchange between units. Conclusion: Overall, the study shows that knowledge management is central for safety behavior.